Review of Ant Colony Optimization for Software Project Scheduling and Staffing with an Event Based Scheduler - Taj, Shireen; Ramana, D. Venkata Swetha (International Journal of Computer Sciences and Engineering, 2014)
Software project scheduling is one of the most important scheduling areas faced by software project management team. For a successful project, both software engineering and software management are very necessary. To complete the software project within a specified time limit, allocate a start and end date that determine the milestones and outcomes of the tasks and, determine which tasks depend on another task to complete its operation. It does the task of save time, build consistency, enhance visibility scheduling is very essential. There are several software project management resources and schedule estimation methods have been developed. Here, represents review of some of these software project scheduling techniques which are used recently and are helpful in handling the various type of scheduling used in software projects.